Elevated local [Ca 2+ ] and CaMKII promote spontaneous Ca 2+ release in ankyrin-B-deficient hearts. Issue 3 (30th April 2016) - Popescu, Iuliana; Galice, Samuel; Mohler, Peter J.; Despa, Sanda
Abstract: Aims: Loss-of-function mutations in the cytoskeletal protein ankyrin-B (AnkB) cause ventricular tachyarrhythmias in humans. Previously, we found that a larger fraction of the sarcoplasmic reticulum (SR) Ca 2+ leak occurs through Ca 2+ sparks in AnkB-deficient (AnkB +/− ) mice, which may contribute to arrhythmogenicity via Ca 2+ waves. Here, we investigated the mechanisms responsible for increased Ca 2+ spark frequency in AnkB +/− hearts. Methods and results: Using immunoblots and phospho-specific antibodies, we found that phosphorylation of ryanodine receptors (RyRs) by CaMKII is enhanced in AnkB +/− hearts. In contrast, the PKA-mediated RyR phosphorylation was comparable in AnkB +/− and wild-type (WT) mice. CaMKII inhibition greatly reduced Ca 2+ spark frequency in myocytes from AnkB +/− mice but had little effect in the WT. Global activities of the major phosphatases PP1 and PP2A were similar in AnkB +/− and WT hearts, while CaMKII autophosphorylation, a marker of CaMKII activation, was increased in AnkB +/− hearts. Thus, CaMKII-dependent RyR hyperphosphorylation in AnkB +/− hearts is caused by augmented CaMKII activity. Intriguingly, CaMKII activation is limited to the sarcolemma–SR junctions since non-junctional CaMKII targets (phospholamban, HDAC4) are not hyperphosphorylated in AnkB +/− myocytes. This local CaMKII activation may be the consequence of elevated [Ca 2+ ] in the junctional cleft caused by reduced Na + /Ca 2+ exchange activity. Indeed, using the RyR-targeted Ca 2+ sensor GCaMP2.2-FBKP12.6, we found that local junctional [Ca 2+ ] is significantly elevated in AnkB +/− myocytes. Conclusions: The increased incidence of pro-arrhythmogenic Ca 2+ sparks and waves in AnkB +/− hearts is due to enhanced CaMKII-mediated RyR phosphorylation, which is caused by higher junctional [Ca 2+ ] and consequent local CaMKII activation.